Performance of Publicly Listed Chilean Firms During the 2008-2009 Global Financial Crisis - Wu, Yi. (Washington, D.C. : International Monetary Fund, 2012)
This paper examines publicly listed Chilean firms' performance during the 2008-09 crisis. In particular, it studies the effects from changes in external financing conditions, aggregate demand, and international trade on firms' investment, sales, and profits, using firm-specific characteristics measured prior to the crisis. The evidence suggests that the crisis had a larger negative impact on firms with greater reliance on external financing, and firms with higher sensitivity to aggregate demand and exports. Firms with more foreign currency debt also had larger declines in sales, although their investment or profits did not differ significantly from other firms.a.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Chile